Salafi-Progressive: Islamic Education Thinking Discourses of K.H. Aceng Zakaria - Selamat, Kasmuri (Dinamika Ilmu, 2020)
This research is aimed to analyze K.H. Aceng Zakaria's thought of Islamic education which is focused on his educational practice to the Organization of Persatuan Islam (Persis) from 1975 to 2006. It's very interesting to study K.H. Aceng Zakaria's thought. At least, there are two reasons: firstly, there wasn't research which raised the aspect of Persatuan Islam's ‘ulama, especially in thought of educational domain, especially from the third generation. Secondly, K.H. Aceng Zakaria is known as an ulama’s of Persis who gives a lot of contribution in education not only the book but also his creativity to hold any alternative educational forum in term of providing people's interest to learn Islamic knowledge. As one of Persis's ulama, his religiosity's thought as same as other Persis ulama identical with purification idea which features as well as Salafi or salafiyyah movement. Based on this study shows, this movement often adhered to the number of stigmatizations, such as rigidity, radical attitude, and some of the similar stigma. The assumption justified when reading a book written by Tsaqil bin Shalfiq al-Qasimi entitled "Rooting out Ahlul Ahwa and Bid'ah". It's the difference from the stigmatizations, through this research, the writer concludes that the consistency of returning Islamic practice to al-Quran and al-Sunnah tends to push progressive attitude. It's proven through educational views of K.H. Aceng Zakaria which focused into an educational book written by K.H. Aceng Zakaria entitled "Zad al-Muta'allim", and his educational practice since he has decided to dedicate his life to the Persis.